Key determinants of “Serious Circumstances” in awarding punitive damages for intellectual property infringement: Evidence from Chinese Judicial Judgments - Kaijie You (PLoS ONE, 2026)
To prevent the over-extension of punitive damages in private law, as has occurred in some common law jurisdictions, China requires the presence of “serious circumstances” as a prerequisite for applying punitive damages in intellectual property infringement cases. However, this requirement still lacks a clear theoretical framework and concrete identification elements. This study illustrates China’s approach by analyzing judicial decisions, and reveals: (1) sixteen elements used by judges to assess the seriousness of intellectual property infringement, which can be consolidated into three key categories: subjective malevolence, degree of conduct, and resulting damage; (2) differences in judicial emphasis across types of intellectual property, with copyright cases focusing on subjective malevolence and industrial property cases emphasizing scale and duration of infringement; (3)cases involving significant social harm are more likely to result in higher punitive damages multipliers; and(4) judges take into account not only the severity of infringement but also the goals and functions of punitive damages.